Aiming for the Bullseye: Targeted activities decrease misconceptions related to enzyme function for undergraduate biochemistry students. Issue 6 (21st August 2021) - Terrell, Cassidy R.; Ekstrom, Thomas; Nguyen, Brian; Nickodem, Kyle
Abstract: Biochemistry curricula present a particular challenge to undergraduate students with abstract concepts which can lead to misconceptions that impede learning. In particular, these students have difficulty understanding enzyme structure and function concepts. Targeted learning activities and three‐dimensional (3D) physical models are proposed to help students challenge these misconceptions and increase conceptual understanding. Here we assessed such pedagogical tools using the Enzyme‐Substrate Interactions Concept Inventory (ESICI) to measure (mis)conceptual changes from Pre‐ to Post‐ time points in a single semester undergraduate biochemistry course. A Control group of students engaged with the active learning activities without the 3D physical models and students in the Intervention group utilized these activities with the 3D physical models. At the Post‐ time point both groups had higher, yet similar ESICI scores of the same magnitude as the highest scoring group from the national sample. Concomitantly, many misconception markers decreased compared to the national sample, although some of these differed between the Control and Intervention groups. Based on this assessment, both pedagogical approaches successfully increased conceptual understanding and targeted many of the misconceptions measured by the ESICI, however, several misconceptions persisted. Surprisingly, the students who used the 3D physical models did not demonstrate a further decrease in the misconception markers. Additionally, psychometric evaluation of the ESICI with our sample recommends the revision of several questions to improve the validity of this assessment. We also offer suggestions to improve instruction and pedagogical tools with further avenues for research on learning.